"A Multimethod and Interdisciplinary Approach to Educating Postsecondary Students on Arctic Challenges and Governance". Issue 3 (3rd July 2021) - Boylan, Brandon M.; Ehrlander, Mary F.; Bouffard, Troy J.
Abstract: Challenges to the Arctic region abound and intersect. Warming, ice and permafrost melting, and pollution jeopardize health and food security of Indigenous and other Northern communities. Problems related to natural resource extraction and shipping are developing. Because these issues cross sovereign boundaries, they must be addressed multilaterally. The Arctic Council is the principal forum in which Arctic states and Indigenous groups address shared concerns in the region. We co-administered a five-day program on science and diplomacy in the Arctic at Dartmouth College in June 2017 to educate postsecondary students on Arctic challenges and governance, foster skills and confidence related to leadership and diplomacy, and inspire civic action in Arctic and international affairs. The program consisted of lectures, discussions, a teamwork and collaboration exercise, a negotiation workshop, and a Model Arctic Council (MAC)—a simulation of delegates' work in the Arctic Council. We found that students had strongly positive perceptions of the curriculum and felt that they accrued Arctic-related awareness and skills, while developing enthusiasm for engaging in civic affairs. Students attributed the program's value to the use of multiple pedagogies, especially simulation, an interdisciplinary environment, and mentorship from and engagement with Arctic Council and other practitioners.